2010
DOI: 10.2343/geochemj.1.0045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic matrices on the determination of the trace element chemistry (Mg, Sr, Mg/Ca, Sr/Ca) of aragonitic bivalve shells (<i>Arctica islandica</i>)&mdash;Comparison of ICP-OES and LA-ICP-MS data

Abstract: The element chemistry of biogenic carbonates can provide important data on past environments. However, the Sr/Ca and Mg/Ca ratios as well as the Mg and Sr concentrations of biological carbonates, especially aragonitic bivalves often depart from apparent thermodynamic equilibrium. When measured in situ by means of LA-ICP-MS, the Mg concentration is often substantially enriched (two-to threefold) near the organic-rich, annual growth lines. To test the hypothesis that some organic components exert a major influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…Heterogeneities in the crystal fabric coincide with heterogeneous distribution of Sr/Ca, Mg/Ca, and Ba/Ca (Schöne et al, 2010Shirai et al, 2014). During the formation of the annual growth lines, extremely slow growth occurs and Sr/Ca and Mg/Ca are seemingly incorporated in equilibrium with the ambient seawater.…”
Section: Potential Methods For Independent Temperature Calibrationmentioning
confidence: 95%
“…Heterogeneities in the crystal fabric coincide with heterogeneous distribution of Sr/Ca, Mg/Ca, and Ba/Ca (Schöne et al, 2010Shirai et al, 2014). During the formation of the annual growth lines, extremely slow growth occurs and Sr/Ca and Mg/Ca are seemingly incorporated in equilibrium with the ambient seawater.…”
Section: Potential Methods For Independent Temperature Calibrationmentioning
confidence: 95%
“…Levels of strontium (Sr) and magnesium (Mg) in bivalve shells have been proposed as proxies for water temperature (Klein et al, 1996;Schöne et al, 2013). However, Sr/Ca and Mg/Ca ratios are still difficult to interpret because the incorporation of trace and minor impurities in the shell carbonate is partly physiologically controlled (e.g., Urey et al, 1951;Purton et al, 1999;Lorrain et al, 2005;Freitas et al, 2005Freitas et al, , 2006Schöne et al, 2010Schöne et al, , 2013Marali et al, 2017a;Geeza et al, 2018). Published results on the relationship between the Sr/Ca and Mg/Ca ratios of bivalve shells and temperature are highly ambiguous; previous studies have reported a positive relationship (Stecher et al, 1996;Hart and Blusztajn, 1998;Toland et al, 2000), negative relationship (Dodd, 1965;Stecher et al, 1996;Surge and Walker, 2006;Schöne et al, 2011), and no relationship (Gillikin et al, 2005;Strasser et al, 2008;Izumida et al, 2011;Wanamaker and Gillikin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of mollusks show that environmental parameters can also influence the microstructure of the shell (Lutz, 1984;Tan Tiu and Prezant, 1987;Tan Tiu, 1988;Nishida et al, 2012) and therefore, can serve as potential proxy for environmental conditions (Tan Tiu, 1988;Tan Tiu and Prezant, 1989;Schöne et al, 2010;Milano et al, 2017b). For example, the size and elongation of individual biominerals in Cerastoderma edule (Milano et al, 2017b) and the cyclical changes in thickness of the outer layer of Scapharca broughtonii (Nishida et al, 2012) shells are related to temperature changes.…”
Section: Introductionmentioning
confidence: 99%
“…Freitas et al, 2006;Gillikin et al, 2005b;Lowenstam and Weiner, 1989) and environmental conditions at the time of deposition (e.g. Ferguson et al, 2011;Gazeau et al, 2010;Hahn et al, 2014;Heinemann, 2011;Henkes et al, 2013;Lowenstam and Weiner, 1989;Schöne et al, 2011). Molluscs are globally distributed and demonstrate sequential growth, thus providing high-resolution seasonal and sub-seasonal records of environmental conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Purton et al, 1999); organic matrix (e.g. Schone et al, 2010;Takesue et al, 2008) and microstructure (overall fabrics) (e.g. Schöne et 30 al., 2013;Shirai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%